ANALISIS BUTIR SOAL STATISTIKA MODEL SUMMATIVE EVALUATION ASSESSMENT MENGGUNAKAN MODEL RASCH - Munali, Munali; Alifah, Siti (LPPM Universitas Bina Bangsa, 2024)
The summative evaluation assessment model is a model combining formative assessment and summative assessment. Learning outcomes in Statistics courses were measured using the summative evaluation assessment model on students of the Information Systems Study Program at Indraprastha PGRI University Jakarta even semester of the 2023/2024 academic year as many as 185 students. The purpose of this study was to analyze the items of the summative evaluation assessment model of the Statistics Course as many as 13 items. This research uses quantitative methodology. Items analysis using the Rasch Model. The results of the study, namely: 1) as many as 4 items fit from 13 items, 2) item 11 is a difficult item with an item measure score of 0.55 logit, and item 12 is an easy item with an item measure score of -0.32 logit, 3) the instrument reliability score of 0.49 shows an unfulfilled category, and 4) the item reliability score of 0.98 shows an excellent category. Based on the results of the study, it can be concluded that the summative evaluation assessment model has not been maximised by lecturers. This is because lecturers have not been maximized in providing feedback on formative assessments and summative assessments. The researcher recommends the next research on how lecturers provide maximum feedback to students on formative assessments and summative assessments.